Defects of class-switch recombination - Notarangelo, Luigi D.; Lanzi, Gaetana; Peron, Sophie; Durandy, Anne (Journal of Allergy and Clinical Immunology, 2006)
Shaping of the secondary antibody repertoire is generated by means of class-switch recombination (CSR), which replaces IgM with other isotypes, and somatic hypermutation (SHM), which allows production of high-affinity antibodies. However, the molecular mechanisms underlying these important processes have long remained obscure. Immunodeficiency with hyper-IgM comprises a group of genetically heterogeneous defects of CSR variably associated with defects of SHM. The study of these patients has allowed us to recognize that both T-cell–B-cell interaction (resulting in CD40-mediated signaling) and intrinsic B-cell mechanisms are involved in CSR and SHM. Elucidation of the molecular defects underlying these disorders has been essential to better understand the molecular basis of Ig diversification and has offered the opportunity to define the clinical spectrum of these diseases and to prompt more accurate diagnostic and therapeutic approaches.